Socio-Economic Status of Tribal Backyard Poultry Rearers in Bastar District of Chhattisgarh - A.K. Chaturvedani , Niranjan Lal , Jitendra Pratap; N.K. Khyalia (Indian Journal of Extension Education, 2017)
The present study was conducted in the Bastar district of Chhattisgarh with the specific objective of finding out the socio-economic profile of the backyard poultry rearers. A multi-stage random sampling procedure was used to select 120 respondents (12 respondents per village) for the study. A structured interview schedule duly pre-tested and validated was used to elicit information from the respondents. The findings of the study revealed that most of the poultry rearers (58.00%) were middle aged belonged to Gond tribe (55.83%) with primary to secondary level education and small size family, agriculture as primary (51.67%) and poultry as secondary occupation (35.38%), with medium flock size (11-16 birds) poultry farms. Majority (84.17%) of the respondents were marginal to small land holding and getting low level of income (67.50%). Majority (51.67%) of the respondents had low level of material possession. The study concludes that the backyard poultry production needs more extension training to enrich their skill and to improve their standard of living.